"Methods of introducing English language" (Journal of Pedagogical Inventions and Practices, 2022)
Foreign Language Teaching Methodology has more than 200 years of history as a science. During this period, it is possible to observe that different attitudes are expressed to the methods of teaching a foreign language. One such view is academic L.V.It is considered to belong to Shcherba. In his opinion, despite the fact that the methodology of teaching any subject is a science, theoretical science is not considered. He will solve practical issues. In particular, the methodology of teaching a foreign language does not only rely on evidence of psychology, but also on general and private linguistic research. This article describes the methods of teaching English.